Experimental study on resilient modulus of liquid silicon dioxide (SI02) stabiuzed subgrade soil - Arumugam, Thillai Nayagee (2009)
Village and estate roads have failed to function due to damage at earlier stage of construction and this required frequent maintenance. Weak sub-grade is the basic factor of exponential damage. In order to overcome this problem, many procedures have been developed to improve the physical behavior (strength or stiffness) of the sub grade soil. One of the procedures is to incorporate a wide range of stabilizing agent, additives or conditioners. Silicon dioxide (Si02) is a water based sodium silicate which is currently being patented on application by Probase Manufacturing Sdn.Bhd. to stabilize subgrade soils. The main objective of this research is to determine the resilient modulus of the liquid Si02 stabilized sub grade soil at number of state conditions (i.e. density, moisture content and amount of stabilizer). Repeated tria"ial load test was carried out at Highway Engineering Laboratory, UTHI'v1. The specimens were prepared with ma"imum (100%), 90% and 95% dry density, optimum moisture content, 3 % dry of optimum and 3% wet of optimum, and the amount of stabilizer was 4%,8% and 12% of dry density of the soil. The specimens were cured for 0, 7, 14 and 28 days to determine the effect of curing days on the stabilized soil. The resilient modulus data were used to identify the best fit equation with the data. However typical pavement system analyzed using KENLA YER for non-linear elastic layer for fine grained soil; the equation applicable is the bilinear equation. Analysis of Variance (ANOVA) has been carried out to evaluate the level of significance effect of the state conditions on the stabilized soil. It has been found that density affects the resilient modulus of fine grained materials: however the magnitude of this effect is smaller compared to effect of moisture conditions. The addition of liquid Si02 stabilizer improves the stiffness (resilient modulus) of the soil and consequently, the optimum concentration is found to be 4% for sub grade stabilization through this study.